CSGID Solves Structures and Identifies Phenotypes for Five Enzymes in Toxoplasma gondii - Lykins, Joseph D.; Filippova, Ekaterina V.; Halavaty, Andrei S.; Minasov, George; Zhou, Ying; Dubrovska, Ievgeniia; Flores, Kristin J.; Shuvalova, Ludmilla A.; Ruan, Jiapeng; El Bissati, Kamal; Dovgin, Sarah; Roberts, Craig W.; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Toxoplasma gondii, an Apicomplexan parasite, causes significant morbidity and mortality, including severe disease in immunocompromised hosts and devastating congenital disease, with no effective treatment for the bradyzoite stage. To address this, we used the Tropical Disease Research database, antisense, crystallography and molecular modeling to identify and characterize a range of potential therapeutic targets for toxoplasmosis. Phosphoglycerate mutase (PGM), nucleoside diphosphate kinase (NDK), ribulose phosphate 3-epimerase (RPE), ribose-5-phosphate isomerase (RPI), and ornithine aminotransferase (OAT) were studied with vivoPMO to interrupt enzyme synthesis, identifying proteins important to parasitic replication and, therefore, of potential therapeutic interest. Targeted vivoPMO against all enzymes resulted in statistically significant perturbation of parasite replication without concomitant host cell toxicity, consistent with a previous CRISPR/Cas9 screen showing PGM, RPE, and RPI contribute to parasite fitness. Crystallography revealed insights into the overall structure, protein oligomeric states and molecular details of active sites important for ligand recognition. Literature and molecular modeling suggested potential inhibitors and druggability. PGM, RPE, and RPI have the greatest promise for affecting replication in tachyzoites. Immunofluorescence assays revealed a posterior and peripheral localization of NDK, suggesting it is secreted. Importantly, many of these targets are shared between other medically important parasites and may have wider therapeutic potential.